Influence of Single Nucleotide Polymorphisms on Rifampin Pharmacokinetics in Tuberculosis Patients - Levin Thomas; Sonal Sekhar Miraj; Mallayasamy Surulivelrajan; Muralidhar Varma; Chidananda S. V. Sanju; Mahadev Rao (MDPI AG, 2020)
Rifampin (RF) is metabolized in the liver into an active metabolite 25-desacetylrifampin and excreted almost equally via biliary and renal routes. Various influx and efflux transporters influence RF disposition during hepatic uptake and biliary excretion. Evidence has also shown that Vitamin D deficiency (VDD) and Vitamin D receptor (VDR) polymorphisms are associated with tuberculosis (TB). Hence, genetic polymorphisms of metabolizing enzymes, drug transporters and/or their transcriptional regulators and VDR and its pathway regulators may affect the pharmacokinetics of RF. In this narrative review, we aim to identify literature that has explored the influence of single nucleotide polymorphisms (SNPs) of genes encoding drug transporters and their transcriptional regulators (SLCO1B1, ABCB1, PXR and CAR), metabolizing enzymes (CES1, CES2 and AADAC) and VDR and its pathway regulators (VDR, CYP27B1 and CYP24A1) on plasma RF concentrations in TB patients on antitubercular therapy. Available reports to date have shown that there is a lack of any association of ABCB1, PXR, CAR, CES1 and AADAC genetic variants with plasma concentrations of RF. Further evidence is required from a more comprehensive exploration of the association of SLCO1B1, CES2 and Vitamin D pathway gene variants with RF pharmacokinetics in distinct ethnic groups and a larger population to reach conclusive information.